Flow cytometric characterization of hematopoietic stem and progenitor cell subpopulations in autologous peripheral blood stem cell preparations after cryopreservation - Heuer, Anabel; Löwhagen, Svea; Uhlig, Stefanie; Hetjens, Svetlana; Büttner, Sylvia; Pflästerer, Britta; Diehlmann, Anke; Klein, Stefan; Klüter, Harald; Bieback, Karen; Wuchter, Patrick (Transfusion medicine and hemotherapy, 2023)
Introduction: Autologous stem cell transplantation is a successful routine procedure with only a small number of non-engraftment cases, although the time to hematopoietic recovery may vary considerably across patients. While CD34 has been the decisive marker for enumerating hematopoietic stem and progenitor cells (HSPCs) for more than 30 years, the impact of CD34-positive cellular subpopulations in autologous HSPC grafts on hematopoietic reconstitution remains unclear. Methods: The two-color ISHAGE protocol represents the current gold standard for CD34+ cell enumeration but includes only the number of viable CD45+/CD34+ cells relative to the body weight of the recipient. We adapted a multicolor flow cytometry marker panel for advanced characterization of CD34 subpopulations in retained samples of autologous peripheral blood stem cell products (n = 49), which had been cryostored for a wide range from 4 to 15 years. The flow cytometric analysis included CD10, CD34, CD38, CD45, CD45RA, CD133, and viability staining with 7AAD. The findings were correlated with clinical engraftment data, including reconstitution of leukocytes, neutrophils, and platelets after transplantation (TPL). Results: We demonstrated that the identification of autologous HSPC subpopulations by flow cytometry after cryopreservation is feasible. Regarding the distribution of HSPC subpopulations, a markedly different pattern was observed in comparison to previously published data obtained using fresh autologous material. Our data revealed the largest ratio of lympho-myeloid progenitors (LMPPs) after freezing and thawing, followed by multipotent progenitors and erythroid-myeloid progenitors. A high ratio of LMPPs, representing an immature stage of differentiation, correlated significantly with early neutrophilic granulocyte and leukocyte engraftment (p = 0.025 and p = 0.003). Conversely, a large ratio of differentiated cells correlated with late engraftment of neutrophilic granulocytes (p = 0.024). Overall, successful engraftment was documented for all patients. Conclusion: We established an advanced flow cytometry panel to assess the differentiation ability of cryostored autologous peripheral blood stem cell grafts and correlated it with timely hematopoietic reconstitution. This approach represents a novel and comprehensive way to identify hematopoietic stem and progenitor subpopulations. It is a feasible way to indicate the engraftment capacity of stem cell products.